Paralytic shellfish toxin producing Aphanizomenon gracile strains isolated from Lake Iznik, Turkey. (15th June 2018) - Yilmaz, Mete; Foss, Amanda J.; Selwood, Andrew I.; Özen, Mihriban; Boundy, Michael
Abstract: Aphanizomenon gracile is one of the most widespread Paralytic Shellfish Toxin (PST) producing cyanobacteria in freshwater bodies in the Northern Hemisphere. It has been shown to produce various PST congeners, including saxitoxin (STX), neosaxitoxin (NEO), decarbamoylsaxitoxin (dcSTX) and gonyautoxin 5 (GTX5) in Europe, North America and Asia. Three cyanobacteria strains were isolated in Lake Iznik in northwestern Turkey. Morphological characterization of these strains suggested all three strains conformed to classical taxonomic identification of A. gracile with some differences such as clumping of filaments, partially hyaline cells in some filaments and longer than usual vegetative cells. Sequences of 16S rRNA gene of these strains were placed within an A. gracile cluster including the majority of PST producing strains, confirming the identification of these strains as A. gracile . These new strains possessed saxitoxin biosynthesis genes sxtA, sxtG and their sequences clustered with those of other A. gracile . Liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis demonstrated the presence of NEO, STX, dcSTX and decarbamoylneosaxitoxin (dcNEO) in all strains. This is the first report of a PST producer in any water body in Turkey and first observation of dcNEO in an A. gracile culture. Highlights: Three cyanobacteria strains were isolated from Lake Iznik, Turkey in 2016. Strains were identified as Aphanizomenon gracile with a polyphasic approach. All three strains produced STX, NEO, dcSTX and dcNEO. First report of a PST producer in Turkish waters. First observation of dcNEO in an A. gracile culture.